(untitled) (Dhaka University Journal of Science, 2024)
This research investigates the incidence and patterns of health problems experienced by tannery employees, as well as the associations between such problems and a variety of other variables. The cross-sectional study was conducted at three randomly selected tanneries of the BSCIC Tannery Industrial Estate in Savar. During in-person interviews, 203 workers were questioned using a questionnaire. Most respondents (84.2%) admitted that they had health problems caused by their jobs. Musculoskeletal disease (65.5%), gastrointestinal problems (38.9%), skin disease (37.9%), respiratory disease (26.6%), and eye disease (17.7%) were the significant causes of illness. Our research revealed that factors such as respondents’ age (p value=.001), experience (p value<.000), working hours (p value=.005), mode of work (p value=.044), types of PPE (p value=.017), and awareness of toxic chemical rules (p value=.033) were significantly associated with health problems among tannery workers. A healthy tannery environment and enhanced medical facilities may improve their health. Dhaka Univ. J. Sci. 72(2): 68-74, 2024 (July)